The Role of Courier Service Quality in Building Customer Satisfaction and Customer Loyalty - Nando Septian; Linda Rahmah Yuliati; Harun Muhyiddin; Ilham P. Hutasuhut (Institute of Computer Science (IOCS), 2022)
This article reports the research results about the influence of Courier Service Quality in building Shopee's Customer Satisfaction and Customer Loyalty who uses Shopee Express delivery in 2020. This research aims to determine whether Courier Service Quality affects Customer Satisfaction positively and significantly and whether Customer Satisfaction affects Customer Loyalty positively and significantly. The research method uses a quantitative approach, data collected using a questionnaire, and data analysis using descriptive and inferential analysis. Inferential analysis using factor analysis and simple linear regression. The result shows: that Courier Service Quality has a positive and significant effect on Customer Satisfaction, and Customer Satisfaction has a positive and significant impact on Customer Loyalty